Methods and systems for processing silicone hydrogel ophthalmic lenses for improved lens transfer - PATTERSON LEAH K; HILL JASON R; MOLOCK JR. FRANK F; WILKINSON THOMAS W (2011)
This invention includes methods and systems for processing silicone hydrogel ophthalmic lenses using aqueous solutions which contain dimethyl siloxane as as processing aids to facilitate lens transfer.